2017
DOI: 10.18203/2320-1770.ijrcog20172530
|View full text |Cite
|
Sign up to set email alerts
|

A study on safety and feasibility of caesarean myomectomy: at a private institute

Abstract: The incidence of myoma associated with pregnancy is reported at 0.3-5%, with a majority of myomas not requiring surgical intervention during pregnancy or delivery. [5][6][7][8] In the pregnant women with coexisting fibroids, there are increased incidences of first trimester losses, pressure symptoms, pain from red degeneration (necrobiosis), torsion of a pedunculated variant, ABSTRACT Background: Myomectomy at the time of caesarean delivery is controversial because of the risk of intractable hemorrhage and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Alternatively, Rai and Mishra, performed a prospective cohort study of 15 patients with different types of myomas including intramural myomas 33.3%, subserosal 26.6%, pedunculated 20%, submucosal 6.6% and myomas on different sites 26.6%. 19 Stepwise devascularization was done in 3 patients without any massive haemorrhage and blood transfusion. None of the patients had postoperative fever, operating time was 15 minutes more than a normal CS with additional 1.5 days hospital stay in patients with CM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Rai and Mishra, performed a prospective cohort study of 15 patients with different types of myomas including intramural myomas 33.3%, subserosal 26.6%, pedunculated 20%, submucosal 6.6% and myomas on different sites 26.6%. 19 Stepwise devascularization was done in 3 patients without any massive haemorrhage and blood transfusion. None of the patients had postoperative fever, operating time was 15 minutes more than a normal CS with additional 1.5 days hospital stay in patients with CM.…”
Section: Resultsmentioning
confidence: 99%
“…The only significant difference was duration of operation (p=0.02) while there was no difference in preoperative, postoperative or mean changes in haemoglobin (p=0.51), duration of hospital stays (p=0.13), transfusion (p=0. 19) and postoperative fever (p=0.66). They concluded that caesarean myomectomy is a safe procedure even in large myomas.…”
Section: Authors Of Publicationmentioning
confidence: 96%